Effectiveness of pelmatoscopia through specialized training and implementation of pelmatoscopicas offices in “Hermilio Valdizan Medrano” hospital and “Carlos Showing Ferrari” hospital, may 2003 - april 2004. Huánuco - Tamayo García, Mónica R. (2009)
The study demonstrated that the techniques used for the taking of plantar impression are not the suitable ones, the same ones that do not guarantee reliability from the legal medical point of view; on the other hand, the process of identification of new born is not fulfilled efficiently, so this process is left unfinished, fulfilling only with the first stage consisting of the capture of the plantar impression on the part of the personnel of health and his corresponding file in clinical history; the expert's report is not realized on the part of the police personnel in the moment of the discharge of the patient; steps that must be realized according to the stipulated thing in the Manual of Proceeding of Personal Identification. Opposite to this problems, it was tried to demonstrated the effectiveness of the pelmatoscopía by means of the use of the suitable skills and the processing logistic resources through a specializing training and the office implementation pelmatoscópicas in the institutions in study. The type and level of investigation are descriptive-explanatory and transversal. Between the main results it was obtained that 100% of the samples picked up (15 pelmatoscópicas sheets) of the personnel who received the training, and at the same time they have the requirements established by the effective norms for a good taking of papiloscópicas impressions; therefore, there is a team of obstetricians professionals that are in the capacity to assume the taking of plantar impression in the identification of the neonatus.